2021
DOI: 10.1136/gutjnl-2020-323126
|View full text |Cite
|
Sign up to set email alerts
|

RNA helicase DDX5 enables STAT1 mRNA translation and interferon signalling in hepatitis B virus replicating hepatocytes

Abstract: ObjectiveRNA helicase DDX5 is downregulated during HBV replication and poor prognosis HBV-related hepatocellular carcinoma (HCC). The objective of this study is to investigate the role of DDX5 in interferon (IFN) signalling. We provide evidence of a novel mechanism involving DDX5 that enables translation of transcription factor STAT1 mediating the IFN response.Design and resultsMolecular, pharmacological and biophysical assays were used together with cellular models of HBV replication, HCC cell lines and liver… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 58 publications
0
30
0
Order By: Relevance
“…B-c0 and B-c5 mainly originated from non-EGC groups while in B-c1, B-c2, B-c3, B-c4 and B-c6, cells from EGC and AG groups predominated (Supplementary Figure 10C). Gene expression analysis showed the similar up-regulated genes between B-c0 and B-c5, DDX5 35 36 , DDX3X 37 and NCL 38 were all anti-pathogens and anti-tumor genes. As plenty of oncogenes significantly up-regulated in B-c1 cluster, we inferred it was deteriorating cell populations induced by tumor cells.…”
Section: Resultsmentioning
confidence: 92%
“…B-c0 and B-c5 mainly originated from non-EGC groups while in B-c1, B-c2, B-c3, B-c4 and B-c6, cells from EGC and AG groups predominated (Supplementary Figure 10C). Gene expression analysis showed the similar up-regulated genes between B-c0 and B-c5, DDX5 35 36 , DDX3X 37 and NCL 38 were all anti-pathogens and anti-tumor genes. As plenty of oncogenes significantly up-regulated in B-c1 cluster, we inferred it was deteriorating cell populations induced by tumor cells.…”
Section: Resultsmentioning
confidence: 92%
“…To determine whether the RNA helicase activity of DDX5 is required for ferroptosis, we employed doxycycline-inducible FLAG-DDX5-HepaRG cell lines (23), encoding WT-DDX5 or the inactive DDX5-K144N mutant lacking ATPase activity (42). Following doxycycline induction, overexpression of WT-DDX5 induced ferroptosis upon addition of sorafenib or RSL3, quantified by cell viability and C11-BODIPY 581/591 assays.…”
Section: Resultsmentioning
confidence: 99%
“…DDX5 is a transcriptional regulator with critical roles in cell growth and differentiation (20), exhibiting diverse functions. In transformed hepatocytes, DDX5 regulates PRC2 function via interaction with lncRNA HOTAIR (22), STAT1 translation by resolving a G- quadruplex located at the 5’UTR of STAT1 mRNA (23), and p62/SQSTM1 degradation markedly reducing its half-life (19).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research suggested that members of the DEAD‐box protein family were involved in the response to ethanol stress and the regulation of antiviral innate immunity. 37 , 38 , 39 , 40 , 41 , 42 Thus, the roles and mechanisms of DDX55 in the development of HCC induced by the known and unknown risk factors are worthy of future studies. Consistent with the involvement of DDX55 in colorectal cancer liver metastasis and in the prognosis of lung cancer patients, we confirmed that DDX55 upregulation correlated with tumor progression and served as an independent prognostic indicator of unfavorable RFS and OS of HCC patients regardless of ethnicity, which represented the most prominent prognostic value among the DEAD‐box protein family.…”
Section: Discussionmentioning
confidence: 99%